Strategically created treaty conflicts and the politics of international law - Ranganathan, Surabhi (Cambridge studies in international and comparative law, 2014)
Treaty conflicts are often deliberately created to challenge or change legal regimes. What does this say about the role of law in international affairs? This book examines modern legal thought and practice, with detailed studies of conflict dynamics in nuclear governance, international criminal justice and the law of the sea.